2014
DOI: 10.1021/ie5008147
|View full text |Cite
|
Sign up to set email alerts
|

Formation of a Compact Protective Layer by Magnesium Hydroxide Incorporated with a Small Amount of Intumescent Flame Retardant: New Route to High Performance Nonhalogen Flame Retardant TPV

Abstract: Magnesium hydroxide (MH) and an intumescent flame retardant (IFR) have been incorporated into a thermoplastic vulcanizate (TPV) for the purpose to fabricate halogen-free flame retardant elastomeric materials. Significant synergistic effects of MH and IFR have been observed for the TPV in terms of both flame retardant properties and mechanical performance. The mechanism of the synergistic effects has been investigated. The results indicate that a small amount of IFR accelerates the degradation of the matrix and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
30
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 29 publications
(30 citation statements)
references
References 35 publications
0
30
0
Order By: Relevance
“…Two HRR peaks were observed for all samples. The first peak as the consequence of ignition and the flame spread on the surface of samples appeared between 60 and 75 s after ignition. The highest peak of 382.94 kW/m 2 at 75 s corresponded to the composites with aluminum hydroxide, and the lowest peak of 293.00 kW/m 2 at 70 s was related to the composites with MAH‐5.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Two HRR peaks were observed for all samples. The first peak as the consequence of ignition and the flame spread on the surface of samples appeared between 60 and 75 s after ignition. The highest peak of 382.94 kW/m 2 at 75 s corresponded to the composites with aluminum hydroxide, and the lowest peak of 293.00 kW/m 2 at 70 s was related to the composites with MAH‐5.…”
Section: Resultsmentioning
confidence: 99%
“…The second peak occurred when the degradation for the surface of samples started, and oxygen entered the inner part of the samples to combust with high efficiency. Finally, a carbonaceous char was formed and occurred in the range from 200 to 330 s. The highest peak of 405.78 kW/m 2 at 280 s was related to the composites with MAH‐5, and the lowest peak of 257.73 kW/m 2 at 330 s was associated with the composites with 1,2‐bis(pentabromophenyl) ethane. The HRR and THR for composites with MAH‐5 and 1,2‐bis(pentabromophenyl) ethane were reduced compared with that of composites without flame retardants.…”
Section: Resultsmentioning
confidence: 99%
“…Considering these problems, many investigations have shown that some minerals, such as MH and MO, can be used as synergistic agents in IFR systems . Recently, the surface modification of nanosized particles has also been studied in order to improve compatibility and dispersity between inorganic particles and polymers …”
Section: Introductionmentioning
confidence: 99%
“…On heating, fire‐retardant materials form foamed cellular charred layers on their surface, which protects the underlying material from the action of the heat flux or the flame. The mechanism is based on slowing up heat and mass transfer between the gas phase and the condensed phase . In most cases, ammonium polyphosphate (APP) is chosen as acid source and blowing agent in IFRs.…”
Section: Introductionmentioning
confidence: 99%